Twenty Fifth Meeting of the National Development Council Summary Record - Planning Commission (Planning Commission, 1968)
In the ‘Central assistance', as estimated, for operational purposes, referred to above, has been included assistance only under the following heads: bonuses on food procurement (now discontinued), grants and loans for the Grow More Food Campaign, special grants to Part 'B' States for development and loans for miscellaneous development. From a preliminary review of the working of the State Plans in 1951-52. and the budgets of the State Governments for 1952-53, it would appear that the task of organising finances to the pattern outlined in the above paragraphs has by and large yet to begin.These considerations as well as the relative merits of the schemes which are now being added on as compared to the schemes which were originally in the State Plans, are matters which deserve close examination. But we must emphasise that the capacity of the Centre to give additional assistance is limited. The whole scheme of Central assistance, as now worked out, may have also to be readjusted in the light of the recommendations of the Finance Commission. All these would have to form part of the pre-assessment of State finances referred to already". At the commencement of the Second Five Year Plan majority of the schemes which were provided in the Central sector but were being implemented by the State outside the Plan were transferred to the State sector and included in the State Plans. The Plan outlays of individual States were decided after discussions between the Planning Commission and the Chief Ministers.
Summary Record
Government of India Planning Commission